Faktor-faktor yang Mempengaruhi Keputusan Pembelian Produk pada Batik Tulis Jati Mas Blora - Navisha Dara Nyuzihadna; Hidup Marsudi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of the study was to determine the effect of Price, Product Quality and Advertising on Purchasing Decisions in Jati Mas Blora, both partially and simultaneously. The research method used a quantitative research design. The population was consumers of Jati Mas Blora batik tulis. The research sample was 100 consumers. The sampling technique used accidental sampling. The data collection technique used a questionnaire. The analysis tools used were instrument tests (validity tests, reliability tests), Classical assumptions (normality tests, multicollinearity and heteroscedasticity tests), Hypothesis tests (multiple linear regression analysis, t-test, F-test and determination coefficient test (R2). The results of the study can be concluded that Price, Product Quality and Advertising on purchasing decisions have a significant effect on public satisfaction in Jati Mas Blora, both partially and simultaneously.